Types of Males’ Compliment Expressions for Indonesian Female Politicians - Duwila, Shanty Anugerah Yuni Puspita Sari; Astutik, Ari; Ardyanti, Erika (Universitas Negeri Semarang, 2024)
The belief that politics is a male-dominated sphere remains strong in Indonesia. However, the increasing participation of women in politics has also received positive appreciation from men. Masculine judgments about women’s potential can be observed through compliments in social media. Behind these compliments lies an implicit message of how men perceive and value women’s presence in the political arena. The purpose of this research is to explore the types of compliments frequently given to Indonesian women involved in politics. The study employs a qualitative descriptive method. Data consists of comments from netizens on the Instagram posts of five Indonesian female political figures. Documentation techniques are used for data collection, while Content Analysis is employed to data analysis. The steps include: 1) selecting political posts, 2) extracting top-liked compliments, 3) identifying types of compliments, 4) categorizing compliments, 5) presenting data, 6) interpreting the, and 7) drawing conclusions. The results show that the compliment types that the women receive from men are in the forms of evaluations or appreciations. The patriarchal system in Indonesia does not serve as a barrier for Indonesian women to actively participate in politics. Men will appreciate and respect women who demonstrate competence and good traits.